Guinea-Bissau : Joint Staff Advisory Note on the Second Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
This paper presents the Joint Staff Advisory Note on Guinea-Bissau's Second National Poverty Reduction Strategy Paper (PRSP II) covering 2011-15. The PRSP II, adopted by the government in July 2011, provides the framework for the implementation of a comprehensive strategy aimed at consolidating macroeconomic stabilization and strengthening recent improvements in economic governance. Its successful implementation would help the country enhance its economic growth conditions, strengthen the rule of law, and accelerate progress toward the achievement of the Millennium Development Goals.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet